Effect of Feeding Low Protein Diets on the Performance of Broiler During Hot-Humid Season - Rahman, Muhammad Siddiqur; Pramanik, Md. Ahsan Habib; Basak, Biplob; Tarafdar, Sharif Uddin; Biswas, Sanjib Kumar (International Journal of Poultry Science, 2001)
An experiment was conducted with 180 randomly selected 7th day old ISA I 757 chicks at Bangladesh Agricultural University, Mymensingh. Four different treatments were considered containing 23, 21, 19, and 17% crude protein respectively. Body weights varied significantly (P<0.01) at 8 weeks of age were 1396.03, 1358.01, 1270.26 and 1175.95 g. Feed conversion ratio also varied (P<0.01) at the end of the experimental period which were 2.34, 2.44, 2.67 and 2.89 for T1, T2, T3 and T4 respectively. Feed consumption, survivability and dressing percent did not vary significantly all over the experimental period. Considering the above result, it may be concluded that 21% crude protein in the diet may be suitable for hot-humid season.